Metabolic syndrome is related to vascular structural alterations but not to functional one both in hypertensives and healthy subjects. (14th October 2021) - Leidi, F; Maloberti, A; Bombelli, M; Monticelli, M; Ruzzenenti, G; Biolcati, M; Giani, V; De Chiara, B; Grassi, G; Giannattasio, C
Abstract: Background: Metabolic Syndrome (MS) has been related to an impairment in arterial structural and functional properties with heterogeneous results. Purpose: In this study we focused on the effects of MS on arterial carotid-femoral Pulse Wave Velocity (PWV) and common carotid Intima Media Thickness (IMT) in two different populations, one of hypertensive patients and one of healthy controls. Methods: We enrolled 816 consecutive hypertensive (HT) and 536 healthy controls. Vascular structural (IMT) and functional (PWV) properties were evaluated. NCEP-ATP-III criteria were used for diagnosis of MS. Results: MS was diagnosed in 26.9% and 6.9% in hypertensive and control subjects, respectively. PWV was similar in controls with and without MS (7.7±1.9 vs 7.6±1.1 m/s, p=0.69), while IMT was higher in controls with than those without MS (0.64±0.18 vs 0.57±0.13 mm, p=0.02). Hypertensives with MS were older (57.9±12.2 vs 52.7±14.1 years, p<0.001) and showed higher PWV (9.0±2.3 vs 8.4±2.1 m/s, p=0.001) and IMT (0.72±0.22 vs 0.65±0.17 mm, p<0.001) than those without MS, however at the age-adjusted analysis only the difference in IMT was confirmed (p=0.007). Regression models showed that MS was an independent determinant of IMT in both controls (β=0.08, p=0.03) and hypertensives (β=0.08, p=0.01), but not of PWV either in controls (β=0.006, p=0.886 and β=0.04, p=0.19, respectively). Conclusions: The main finding of our work is that MS is a significant determinant of IMT while this is not the case for PWV. This result has been confirmed both in hypertensive subjects and in healthy controls. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): ASST Grande Ospedale Metropolitano Niguarda